Các yếu tố xác định mức độ công bố thông tin công cụ tài chính của ngân hàng thương mại tại Việt Nam - Nguyễn Thị Thu , Hiền; Nguyễn Thị Ngọc, Tú; Lê Hữu Thành, Tài; Huỳnh Minh Gia, Hào; Nguyễn Bảo , Trâm; Lê Yến, Bình (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
This study aims to investigate the required Financial instrument disclosure (FID) checklist and the determining factors of the degree of FID at commercial banks in Vietnam. Regarding Vietnamese bank’s accounting regulations, content analysis in particular, the study has identified 107 articles of FID across 5 categories: Accounting policy disclosures, balance sheet disclosures, income statement disclosures, hedging and derivatives disclosures and fair value measurement disclosures. Based on the level of FID on Financial Statements of 23 commercial banks in Vietnam between 2016 and 2020, the findings show that the level of disclosure on financial instruments in commercial bank’s financial reporting is low (41%), and there are discrepancies amongst banks and that many requirements are overlooked by banks. The study also demonstrates that the effects of audit quality and bank size are directly proportional, whereas the state ownership and the size of the Board of Directors tend to have an adverse impact on the disclosure level of financial instruments in commercial banks. Finally, the study suggests measuring corporate governance should be considered in future studies.
Keywords: Financial Instrument accounting; Disclosure; IFRS7; Commercial bank